Gower's principles of modern company law - Davies, P. L. (Sweet & Maxwell, 1977)
Gower has long been recognised as the leading text on company law, its lucid analysis and accessible style being of great assistance and encouragement to all those involved in this area. Gower's undisputed strength lies in covering the considerable breadth of company law by way of a detailed, in-depth analysis.